NEURODIVERGENT LANGUAGE LEARNING WITH AI: SUPPORTING ADHD AND AUTISM - Raxmatullayeva Gulgina Zafarovna (“SUN’IY INTELLEKTNING TIL O‘RGANISHDAGI O‘RNI” MAVZUSIDA TALABALAR ILMIY-AMALIY KONFERENSIYASI, 2025)
In today's diverse educational environment, supporting neurodivergent students- particularly those with Attention Deficit Hyperactivity Disorder (ADHD) and Autism Spectrum Disorder (ASD)—is no longer optional but essential. This paper explores the intersection of Artificial Intelligence (AI) and foreign language learning for neurodivergent learners. It talks about the real challengesthey face , how AI tools can adapt to their needs, and how we can create better learning experiences for them. The findings show that AI, if used wisely, can help turn struggles into success and loneliness into social skills. This article offers practical insights and recommendations for educators, developers, and policy-makers.